2022
DOI: 10.1136/bmjopen-2021-058013
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of mental ill-health in tuberculosis patients under treatment in a rural province of South Africa: a cross-sectional survey

Abstract: ObjectivesTuberculosis (TB) remains prevalent despite the availability of effective anti-TB medications, and accumulating evidence suggests a high rate of mental disorders in people with TB. This is because TB and psychiatric disorders share several risk factors, such as poverty, homelessness and substance use disorder. Moreover, psychiatric comorbidities in patients with TB are associated with poor treatment outcomes. This study explored the psychiatric comorbidity and clinical correlates in individuals recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…These socioeconomic factors can therefore create a feedback loop with physical health, in which the absence of one worsens the other and delays recovery. This feedback loop can be compounded by worsened mental health, and unemployment, underemployment, and poverty in TB patients has been associated with multiple mental illnesses, including the anxiety, social anxiety, and depression noted by participants in this study [11].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These socioeconomic factors can therefore create a feedback loop with physical health, in which the absence of one worsens the other and delays recovery. This feedback loop can be compounded by worsened mental health, and unemployment, underemployment, and poverty in TB patients has been associated with multiple mental illnesses, including the anxiety, social anxiety, and depression noted by participants in this study [11].…”
Section: Discussionmentioning
confidence: 78%
“…Most South Africans live in areas that are subjected to high levels of poverty, unemployment, poor housing, and sanitation [10]. Mental illness and substance use places additional burdens on TB patients, with one recent study nding an 82% prevalence rate for mental disorders, including depression, anxiety, and substance use, among participants [11]. All these factors have a role in driving the status quo of TB in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The 48.5% prevalence of any mental illness is higher compared to findings of a study in Pakistan with a rate of 31%, Nigeria at 32% and a pooled rate of 34% in a meta-analysis [ 19 , 33 , 34 ]. It is however lower than 82% rate in South Africa [ 35 ]. Prevalence of mental illness among patients on treatment for TB is anticipated to be higher due to shared risk factors including alcohol use, smoking, overcrowding, stigma, association with HIV, psychosocial and economic stressors or due to compromised immunity and neglected self-care associated with mental illness [ 25 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent South African study examining patients with TB in primary care found that 83% screened positive for a psychiatric diagnosis, with depression among the most common diagnoses, and 43% screened positive for a SU disorder. Over half of these patients were concurrently living with HIV, with similar rates of psychiatric and SU diagnoses identified in these patients [ 13 ]. In other studies, rates of depression have been estimated to be as high as 41% among people with HIV [ 9 ] and 64% among people with TB in South Africa [ 14 ].…”
Section: Introductionmentioning
confidence: 99%